Surgical Site Infection Risk Factor Analysis in Postbariatric Patients Undergoing Body Contouring Surgery: A Nested Case-Control Study. Issue 5 (May 2019) - Wiser, Itay; Plonski, Lori; Shimon, Nitai; Friedman, Tali; Heller, Lior
Abstract : Background: Surgical site infections (SSIs) following body-contouring plastic surgery pose a significant burden on patients and caregivers, possibly leading to undesired surgical outcomes. Surgical site infection incidence following body-contouring plastic surgery ranges from 2% to 7%, but is estimated much higher among postbariatric massive weight loss (MWL) patients. Objective: The aim of this study was to evaluate SSI rate, risk and protective factors among postbariatric MWL patients following body-contouring plastic surgery. Methods: This was a nested case-control study of MWL patients who underwent body-contouring plastic surgery at the Department of Plastic Surgery at Assaf Harofeh Medical Center, between 2007 and 2014. Data were obtained from medical records. Surgical site infection was defined according to the Centers for Disease Control and Prevention criteria. Logistic regression was conducted to assess independent risk factors for SSIs. Results: From a cohort of 172 patients, 86 were included in the study. Surgical site infection rate was 20% (n = 17). Significant SSI risk factors included lifetime maximal weight and lifetime maximal body mass index ( P = 0.039 and P = 0.002, respectively), body mass index loss prior to surgery ( P = 0.032), estimated blood loss during surgery ( P = 0.002), and gynecomastia repair procedure ( P = 0.038). Independent SSI-associated factors included thigh lift procedure (odds ratio, 4.66; 95% confidence interval, 1.13–19.28) and preoperative antimicrobial prophylaxis (odds ratio, 0.04; 95% confidence interval, 0.03–0.61). Conclusions: Although not required by current guidelines for body-contouring plastic surgery, preoperative antimicrobial prophylaxis in our study demonstrated a significant protective effect against SSIs. Further research may reveal its true contribution to SSI prevention in body-contouring plastic surgery.